2019
DOI: 10.1021/acscatal.8b04885
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing High Metal Loadings of Thermally Stable Platinum Single Atoms on an Industrial Catalyst Support

Abstract: Single-atom catalysts have attracted attention because of improved atom efficiency, higher reactivity, and better selectivity. A major challenge is to achieve high surface concentrations while preventing these atoms from agglomeration at elevated temperatures. Here we investigate the formation of Pt single atoms on an industrial catalyst support. Using a combination of surface sensitive techniques such as XPS and LEIS, X-ray absorption spectroscopy, electron microscopy, as well as density functional theory, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
286
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 272 publications
(330 citation statements)
references
References 46 publications
27
286
1
Order By: Relevance
“…We note that despite the elevated temperature under oxidizing conditions, Kunwar et.al. demonstrated that Pt is trapped as single atoms on the HSA ceria and that up to 3 wt % Pt can be loaded in the form of single atoms . Before the characterization and kinetic measurements, the catalyst was first oxidized in 20 kPa O 2 (99.999 % Airgas) balanced with He (99.999 % Airgas, equipped with moisture/O 2 trap, Agilent OT3‐2) at 400 °C for 30 min, then flushed with He for 10 min and cooled down to room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that despite the elevated temperature under oxidizing conditions, Kunwar et.al. demonstrated that Pt is trapped as single atoms on the HSA ceria and that up to 3 wt % Pt can be loaded in the form of single atoms . Before the characterization and kinetic measurements, the catalyst was first oxidized in 20 kPa O 2 (99.999 % Airgas) balanced with He (99.999 % Airgas, equipped with moisture/O 2 trap, Agilent OT3‐2) at 400 °C for 30 min, then flushed with He for 10 min and cooled down to room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…demonstrated that Pt is trapped as single atoms on the HSA ceria and that up to 3 wt % Pt can be loaded in the form of single atoms. [11] Before the characterization and kinetic measurements, the catalyst was first oxidized in 20 kPa O 2 (99.999 % Airgas) balanced with He (99.999 % Airgas, equipped with moisture/O 2 trap, Agilent OT3-2) at 400°C for 30 min, then flushed with He for 10 min and cooled down to room temperature. To transform the Pt single atoms present in the as synthesized catalyst [6b,11] into Pt nanoparticles, the catalyst was reduced at 300°C for 40 min in 2.5 kPa CO (5 %CO, balance N 2 , certified grade Airgas) balanced with He at 30 sccm total flowrate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[59][60][61] The intensity of the first peak after absorption edge, so-named as White Line (WL), represents the vacancy in the 5d orbitals of the 5d-metal atoms and can be used for the estimation of its oxidation state. Using the XANES spectra of reference Pt 4 + compounds (individual nitrato complexes) and data from the literature for Pt(acac) 2 (Pt 2 + ), [9,62,63] it can be concluded that the oxidation state of Pt is close to Pt 2 + for the "PtO x /CeO 2 -220" catalyst after activation and at the different temperatures during the catalytic reaction. For the as-prepared catalyst the oxidation state of Pt is less than 4 + but higher than 2 + , this is in a good agreement with the XPS data ( Figure 9, Table 2).…”
Section: Operando Xafs Study Of Pto X /Ceo 2 Catalystsmentioning
confidence: 99%
“…[1,2] Particularly, catalysts containing platinum deposited on ceria were found to provide an excellent CO conversion at moderate temperatures, keeping their activity after hightemperature stresses. [3][4][5][6][7][8][9][10] The PtÀ Ceria interaction lowers the reaction ignition temperature, which is crucial for preventing air pollution when an engine starts or for autonomous air cleaning systems.…”
Section: Introductionmentioning
confidence: 99%